Turbulent Flow Promotes Cleavage of VWF (von Willebrand Factor) by ADAMTS13 (A Disintegrin and Metalloproteinase With a Thrombospondin Type-1 Motif, Member 13). Issue 9 (September 2019) - Bortot, Maria; Ashworth, Katrina; Sharifi, Alireza; Walker, Faye; Crawford, Nathan C.; Neeves, Keith B.; Bark, David; Di Paola, Jorge
Abstract : Objective—: Acquired von Willebrand syndrome is defined by excessive cleavage of the VWF (von Willebrand Factor) and is associated with impaired primary hemostasis and severe bleeding. It often develops when blood is exposed to nonphysiological flow such as in aortic stenosis or mechanical circulatory support. We evaluated the role of laminar, transitional, and turbulent flow on VWF cleavage and the effects on VWF function. Approach and Results—: We used a vane rheometer to generate laminar, transitional, and turbulent flow and evaluate the effect of each on VWF cleavage in the presence of ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type-1 motif, member 13). We performed functional assays to evaluate the effect of these flows on VWF structure and function. Computational fluid dynamics was used to estimate the flow fields and forces within the vane rheometer under each flow condition. Turbulent flow is required for excessive cleavage of VWF in an ADAMTS13-dependent manner. The assay was repeated with whole blood, and the turbulent flow had the same effect. Our computational fluid dynamics results show that under turbulent conditions, the Kolmogorov scale approaches the size of VWF. Finally, cleavage of VWF in this study has functional consequences under flow as the resulting VWF has decreased ability to bind platelets and collagen. Conclusions—: Turbulent flow mediates VWF cleavage in the presence of ADAMTS13, decreasing the ability of VWF to sustain platelet adhesion. These findings impact the design of mechanical circulatory support devices and are relevant to pathological environments where turbulence is added to circulation. Abstract : Supplemental Digital Content is available in the text.